Addressing corruption through legal reform: Exploring connections and pathways for change - Кубаєнко, Андрій Володимирович; Кубаєнко, А. В.; Kubaienko, Andrii V.; Yuzyuk, Andriy; Vasylchyshyn, Oleksandra; Zarichanskyi, Oleh; Pidpala, Iryna (Mossoró : Malque Publishing, 2024)
This article explores how corruption and the legal system interact, focusing on possible ways to reform anti-corruption efforts. The authors analyse the impact of corruption on the effectiveness of legal institutions and processes. They also evaluate various strategies and measures to mitigate corruption in the legal sector. The study examines internal and external factors affecting corruption in the legal system. It offers practical recommendations for developing effective mechanisms for controlling and curbing corruption in law enforcement and judicial bodies. The article aims to analyse the interrelationships and find possible ways to reform and prevent corruption in the legal system. The paper presents a structural scheme for determining how corruption and the legal system interact and describes possible ways of reform. Such methods as observation and analysis of practices and experimental research were employed in the study. The authors analyse various aspects of corruption in the legal sector, including its causes, consequences, and methods of counteraction. The paper also discusses the mechanisms of legislative, administrative, and institutional reforms aimed at strengthening the legal system and preventing corruption. The authors offer a set of practical recommendations for improving the effectiveness of the legal system and fighting corruption, taking into account the specifics of different legal traditions and contexts. The authors present a model of the interrelation between the legal system and corruption and ways of reforms to address it. A study was conducted to assess the adequacy of the model linking the legal system and corruption, as well as reform pathways, through a survey of 62 legal system representatives. The research was carried out in three stages, during which the causes of corruption, approaches to reforming the legal system, and methods for combating corruption were identified. Subsequently, the most effective methods for combating corruption were highlighted according to the outlined evaluation criteria.
Yuzyuk A. Addressing corruption through legal reform: Exploring connections and pathways for change / A. Yuzyuk, O. Vasylchyshyn, O. Zarichanskyi et al. // Multidisciplinary Reviews. – Mossoró : Malque Publishing, 2024. – 8(SI). – № e2024spe082. Режим доступу: https://hdl.handle.net/11300/32331
Keywords: corruption; law enforcement; judicial bodies; justice system; control mechanism; prevention of corruption